Study of the effects of climatic conditions on the phenolic content and antioxidant activity of Austrian and Montenegrin red wines - Reinhard Eder; Radmila Pajović Šćepanović; Danijela Raičević; Tatjana Popović; Karin Korntheuer; Silvia Wendelin; Astrid Forneck; Christian Philipp (OENO One, 2023)
We evaluated the chemical composition and antioxidant activity of 30 red wines from Austria (cv. Cabernet-Sauvignon, Blaufraenkisch and Zweigelt) and 20 wines from Montenegro (cv. Cabernet-Sauvignon and Vranac) from three consecutive vintages: 2014, 2015 and 2016. We determined spectrophotometrically the contents of total phenol (TP), total anthocyanin (TA) and low- and high-molecular-weight proanthocyanidins (LMP and HMP respectively). We identified and quantified 18 phenolic compounds (hydroxycinnamic acids, hydroxybenzoic acids, stilbenes and flavan-3-ols) by high-performance liquid chromatography. In addition, we used Fourier-transform infrared spectroscopy for chemical analyses of the main wine parameters. Austrian autochthonous wines exhibited a similar chemical composition (alcohol 12.4 vol%, pH 3.38). Blaufraenkisch wines showed higher TP, HMP and LMP than Zweigelt wines; however, TA content was similar. Blaufraenkisch wines also showed higher phenolic acid, flavan-3-ol and stilbene contents than Zweigelt wines. Montenegrin autochthonous Vranac wines showed a typical chemical composition (alcohol 13.0 vol%, pH 3.42), and medium to high levels of phenols: TP, HMP, LMP, TA, HCA and flavan-3-ols. On the other hand, they showed a moderate stilbene content. Cabernet-Sauvignon wines from Austria and Montenegro exhibited some similarities in phenolic composition: TP, HMP, LMP and TA. There were notable variations in the phenolic acid and flavan-3-ol contents, especially the stilbene content, which was much higher in the Austrian wines than in the Montenegrin wines. These findings evidence an important impact of climatic conditions on these compounds. The antioxidant activity in all investigated wines was high and correlated strongly with TP, total phenol index, HMP and LMP in wines. The vintage influenced the chemical composition and content of all examined phenolic groups, except flavan-3-ols. Wines from the vintage with the best maturity (2015) contained the highest content of spectrophotometrically determined phenolic compounds and lowest level of phenolic acids and stilbenes. Principle component analysis showed that wines were mainly discriminated by variety and origin but not by vintage.